Experiences of perinatal genetic screening for people from migrant and refugee backgrounds: a scoping review - Kanga-Parabia, Anaita; Archibald, Alison D.; Biggs, Laura J.; Lewis, Sharon; Tutty, Erin; Dawson-McClaren, Belinda (European journal of human genetics : EJHG, 2025)
People from refugee and migrant backgrounds often face poor experiences and outcomes in healthcare, and genetic healthcare is no exception. Understanding whether and how these health inequities manifest is an important step towards equitable perinatal genetic screening for genetic or chromosomal conditions (offered preconception, prenatally, or during the newborn period). A scoping review was conducted to review international evidence of perceptions and experiences of perinatal genetic screening for people from migrant and refugee backgrounds. Search strategies were applied to Medline, Embase, and CINAHL databases to identify articles meeting eligibility criteria. Evidence was synthesised using descriptive and content analysis, with theoretical frameworks of proportionate universality and relational autonomy used to interpret findings. Of 11,046 unique articles identified, twenty-six met inclusion criteria and underwent full-text review. Most studies were set in Western countries, and participants were primarily born in Asia, South America, or Africa. Studies indicated varying awareness, knowledge, attitudes, and uptake of screening. Several studies highlighted a lack of adequate in-language resources, the use of concepts that were unrecognised in particular communities, and poor interactions with healthcare providers. Strategies to address the above issues included person-centred counselling, increased consultation time, access to interpreters, and training for relevant providers. Other recommendations included addressing structural, financial, and geographical barriers to improve access to screening and associated care. Whilst additional research is required, we propose evidence and theory-informed strategies to improve perinatal genetic screening services for people from migrant and refugee backgrounds.